2022
DOI: 10.21926/obm.icm.2203040
|View full text |Cite
|
Sign up to set email alerts
|

Self-Hypnosis for Phantom Limb Pain: A Multiple-Case Study

Abstract: Phantom limb pain occurs in more than half of the people who have undergone an amputation. Hypnosis can alleviate pain effectively in experimental, procedural, and chronic pain. Thus, in this multiple-case study, we determined whether hypnosis might be a successful complementary approach to help patients with phantom limb pain in alleviating their pain quality (i.e., sensitive and affective), intensity, fatigue, and emotional distress (i.e., anxiety and depression). Seven patients experiencing phantom limb pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…Studies focusing on the use of hypnosis in healthy subjects and patients with acute or chronic pain highlighted a modulation of pain perception during the hypnotic state ( Rainville, 1997 ; Vanhaudenhuyse et al, 2018 ; Bicego et al, 2021 ). A multiple-case study found that self-hypnosis could also be a useful tool to improve the quality of life of patients suffering from phantom limb pain (i.e., sensation of pain in a limb that has been amputated) by reducing the intensity of the pain, whether sensory or affective ( Bicego et al, 2022 ). The reduction of pain sensation induced by hypnosis allows decreasing the doses of analgesics usually administered to these patients and thus improves their level of arousal and quality of life.…”
Section: Pain and Nociception Assessment And Management In Doc And Lismentioning
confidence: 99%
“…Studies focusing on the use of hypnosis in healthy subjects and patients with acute or chronic pain highlighted a modulation of pain perception during the hypnotic state ( Rainville, 1997 ; Vanhaudenhuyse et al, 2018 ; Bicego et al, 2021 ). A multiple-case study found that self-hypnosis could also be a useful tool to improve the quality of life of patients suffering from phantom limb pain (i.e., sensation of pain in a limb that has been amputated) by reducing the intensity of the pain, whether sensory or affective ( Bicego et al, 2022 ). The reduction of pain sensation induced by hypnosis allows decreasing the doses of analgesics usually administered to these patients and thus improves their level of arousal and quality of life.…”
Section: Pain and Nociception Assessment And Management In Doc And Lismentioning
confidence: 99%